COMPARATIVE STUDY OF THE DEVELOPMENT OF UNTING THOUGHT AROUND THE STABILITY OF THE MONETARY UNIT AT THE MICRO AND MACRO LEVELS - Sharaf, Dr. Hussein (Dirasat in Economics and Business, 1972)
At the micro level the factors underlying the development of accounting thought around the assumption of a stable monetary unit Are analyzed in terms of three environmental situations : (i) conditions of hyper-inflation. (ii) the implications of fast technological changes in industry, and (iii) the cumulative effects of a gradual decline in the purchasing power of money. At the macro level the effects of price-level changes upon the measurement of the main aggregates at current prices are outlined and the attempts to eliminate such effects are stated in the order of the development of thought in that field. The difficulties encountered in achieving this purpose together with proposed solutions are explained. The accuracy of results is examined and evaluated.